Assessing weightlifting bar mechanical characteristics - Chiu, L. (The Journal of Strength and Conditioning Research, 2010)
Weightlifting bars are among the most versatile implements in strength and conditioning, allowing numerous exercises, such as squats, cleans and snatches to be performed. Although generally considered a rigid object, empirical evidence and recent research indicates that the weightlifting bar deforms when loaded and/or is lifted with sufficient velocity. The purpose of this investigation was to assess the mechanical characteristics of eight weightlifting and one general purpose weight training bar. Bar deformation was tested using a modified four-point bending method. Portable squat stands were placed 66.2cm apart and bars centered across the stands to simulate the pulling phase of the clean. Bars were loaded and unloaded in two cycles by adding 25kg rubber bumper plates. Plates were added in pairs (i.e. left and right ends), allowed to settle for 1 minute, and an image was taken using a digital camera. Deformation of bars was determined as the difference in height between the center of the bar and a horizontal line through the left and right ends of the bar. Bending moment about the center of the bar was estimated using static calculations. Apparent barbell stiffness was calculated as the slope of bar deformation (x-axis) versus bending moment (y-axis) plots. All bars displayed linear hysteresis plots, characteristic of elastic (such as steel) rather than viscoelastic materials. Three of the bars, the make of which have been used in elite international competition (i.e. world championships and Olympics) were set as criterion for appropriate stiff ness. These bars had an apparent stiffness of 299N[middle dot]m[middle dot]cm-1, 347N[middle dot]m[middle dot]cm-1 and 350N[middle dot]m[middle dot]cm-1. The latter two bars were identical model bars from one manufacturer. Four other bars tested had an apparent stiffness between the low and high end of the criterion (313N[middle dot]m[middle dot]cm-1, 321N[middle dot]m[middle dot]cm-1, 335N[middle dot]m[middle dot]cm-1 &338N[middle dot]m[middle dot]cm-1. Two bars had an apparent stiffness greater than the high end of the criterion (356N[middle dot]m[middle dot]cm-1 & 384N[middle dot]m[middle dot]cm-1). The latter bar also had a larger diameter than the other bars (30mm vs. 28mm). DISCUSSION: Anecdotally, the bar with the lowest apparent stiffness is reported by weightlifters to have the greatest spring. Alternately, the bars used for the high end of the criterion are reported to have a high stiffness, thus the current data support these subjective reports. As these bars have been used in elite international competition, they can be used as a criterion for bar mechanical characteristics. Bars with an apparent stiffness between these bars would be appropriate for use when performing weightlifting exercises, such as in an athletic performance training program. Bars with greater apparent stiffness may not be appropriate for weightlifting exercises, but may be used when less bar deformation is desired. As the mechanical properties of bars differ between manufacturers, not all bars are appropriate for weightlifting exercises. Appropriate equipment should be used for exercises such as cleans, snatches, and jerks, to allow proper execution and technique, and possible minimize the risk of injury.